Assessment and management of elemental mercury poisoning—a case report. Issue 2 (17th January 2017) - Bazoukis, George; Papadatos, Stamatis S.; Michelongona, Paschalia; Fragkou, Archodula; Yalouris, Athanasios
Key Clinical Message: We describe a patient with elemental mercury aspiration and retention in the appendix after elemental mercury ingestion. Conservative management was proved to be successful for the removal of the mercury from the appendix while we do not suggest bronchoalveolar lavage in cases of small amount elemental mercury aspiration. Abstract : We describe a patient with elemental mercury aspiration and retention in the appendix after elemental mercury ingestion. Conservative management was proved to be successful for the removal of the mercury from the appendix while we do not suggest bronchoalveolar lavage in cases of small amount elemental mercury aspiration.